Assessment of Climate Smart Agricultural Practices (CSAP) Adopted by Crop Farmers in Adapting to Climate Change and Environmental Issues in Zamfara State, Nigeria - Alhassan, Y. J.; Sanchi, I. D.; Ikpe, E; Norbert, S (Discoveries in Agriculture and Food Sciences, 2023)
This study assessed the Climate Smart Agricultural Practices (CSAP) adopted by arable crop farmers in adapting to climate change and environmental issues in Zamfara State, Nigeria. Multistage sampling techniques was used to select six local government areas in the state. Three hundred and fifty (350) farmers were randomly selected and administered questionnaire. Sets of standardized questionnaires survey and interview were used to elicit information on CSAP from the farmers. The data were analyzed using descriptive statistics, Total Factor Productivity (TFP), and Least Squares Regression (LSR). The analysed results were presented on tables and charts. The results show that the prevalent CSAP adopted by the farmers were: cover cropping, application of organic manures, adoption of minimum tillage, practice of crop rotation with legumes, usage of mulching, application of inorganic fertilizers and planting of improved seed varieties. Results of the determinants of TFP estimate reveals that age (-1.328), education (0.427), farm size (0.41), organic fertilizer (0.48), access to extension services (0.342), cover cropping (0.023), inorganic fertilizer (.47), improved seed varieties (0.503), crop rotation with legumes (0.54), access to credit facilities (0.273) significantly contribute to productivity at different levels of significance in the study area. While age impacted negatively on productivity, all others impacted positively on productivity. The study concluded that CSAP had positive impacts on crop productivity. The study recommends the adoption of sustainable CSAT such as the use of organic and inorganic fertilizer, cover cropping, and the use of improved seed varieties; provision of agricultural credit facilities to the farmers and availability of extension workers in the study area.